ANALYSIS OF INSULATION TRANSFORMERS SYSTEM RISKS FROM SWITCHING OVERVOLTAGES - Pająk, Piotr (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
Intensive devlopment in the area of vacuum switches, usage of vacuum as a extinguishing element, as well as progress in the area of contact materials contributed to broad usage of vacuum circuit breakers in energetics. However, vacuum cicuit breakers show adverse characteristics that affect switching surge waveforms, which appear on switching objects. The article presents results of computer simulations and test results of overvoltages generated during switching off by vacuum circuit breakers. Influence of metal oxide surge arresters will be also presented.